PERLINDUNGAN HUKUM TERHADAP INVESTOR AKIBAT AKTIVITAS FINANCIAL BETTING DAN TURUNANYA MELALUI APLIKASI ONLINE DI INDONESIA - Dika Anggara Putra (JURNAL KEADILAN HUKUM, 2023)
In the era of digital technology disruption 4.0, forcing people in the world, especially in Indonesia to use digital technology in almost all daily activities, especially the arrival of the Covid 19 pandemic accelerated the development of digital technology and forced almost all people to use it. This includes the revolutionary financial sector using digital technology as a means for interaction between debtors and creditors as well as investors in carrying out financial activities. The rapid pace of technological development, especially in the financial sector, should be balanced with the development of laws and regulations governing digital economic activities so that in the implementation of digital economic activities, especially in the financial sector, the Indonesian people are protected by legal rules to ensure the implementation of digital technology activities in accordance with the principle of justice.